The distributions of sums of the prime indicators with respect to distinct frequencies - Šiaulys, Jonas (Lietuvos matematikos rinkinys, 2004)
A characterization of a set of strongly additive functions fx which has the same limit law with respect to ordinary and logarithmic frequencies is obtained. Strongly additive functions which take zero or unit for each prime p are considered.